Pengelolaan Media Sosial Instagram @jabarsaberhoaks oleh Tim Jabar Saber Hoaks dalam Menanggulangi Berita Hoaks terhadap Masyarakat Jawa Barat - Dermawan, Syifa Fauziyah; Nugraha, Aat Ruchiat (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The purpose of this research is to find out how the management of Instagram @jabarsaberhoaks carried out by the Jabar Saber Hoaks Team in tackling hoax news to the people of West Java. The writing method used is a qualitative method with the social media planning model The Circular Model of SoMe initiated by Regina Luttrell. Based on the results of observations and interviews, Instagram @jabarsaberhoaks at the share stage can create content that is relevant to the issues circulating in the community and build public trust in the Jabar Saber Hoaks Unit. At the optimize stage, Instagram @jabarsaberhoaks responsively receives and responds to complaints from the public through the direct message feature regarding issues that require fact checking and digital literacy. At the manage stage, the Jabar Saber Hoaks Team conducts media monitoring through the Instagram insight feature, and conducts quick responses. At the engage stage, Instagram @jabarsaberhoaks collaborates with other West Java Saber Hoaks Instagram accounts in publishing content. The conclusion that can be drawn is that the management of Instagram @jabarsaberhoaks has met several SoMe Model criteria, but needs to meet the aspects of optimizing all Instagram features, tools and using influencer relations.